2020
DOI: 10.1177/2045125320973794
|View full text |Cite
|
Sign up to set email alerts
|

Association between plasma levels of BDNF and the antisuicidal effects of repeated ketamine infusions in depression with suicidal ideation

Abstract: Background: This study is the first to examine the association between plasma levels of brain-derived neurotrophic factor (BDNF) and the antisuicidal effects of repeated ketamine infusions in depressed patients with suicidal ideation. Methods: Fifty-seven depressed patients with suicidal ideation received six ketamine infusions (0.5 mg/kg) during a 12 days period. Suicidality was measured with the Scale for Suicidal Ideations (SSI-part 1), item 10 of the Montgomery–Åsberg Depression Rating Scale (MADRS), and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…Depressive symptoms of patients correlated with BDNF plasma levels for up to 72 h ( 128 ), while one found no correlation with mood responses ( 129 ). Other studies have found no differences in BDNF levels in plasma at the same time points despite significant improvements in mood ( 129 133 ). In a genome-wide association study, single nucleotide polymorphisms as well as whole genes involved in BDNF-TrkB signaling were shown to be associated with rapid and sustained antidepressant effects in patients with TRD ( 134 ).…”
Section: Resultsmentioning
confidence: 75%
“…Depressive symptoms of patients correlated with BDNF plasma levels for up to 72 h ( 128 ), while one found no correlation with mood responses ( 129 ). Other studies have found no differences in BDNF levels in plasma at the same time points despite significant improvements in mood ( 129 133 ). In a genome-wide association study, single nucleotide polymorphisms as well as whole genes involved in BDNF-TrkB signaling were shown to be associated with rapid and sustained antidepressant effects in patients with TRD ( 134 ).…”
Section: Resultsmentioning
confidence: 75%
“…This study was part of a longitudinal and open‐label trial using ketamine for depression, conducted at the Affiliated Brain Hospital of Guangzhou Medical University (Chen et al, 2021; Y. L. Zhou et al, 2020; Zheng et al, 2020). This clinical trial was approved by the Clinical Research Ethics Committees of the Affiliated Brain Hospital of Guangzhou Medical University and was registered at http://www.chictr.org.cn/ (registration number: ChicCTR‐OOC‐17012239).…”
Section: Methodsmentioning
confidence: 99%
“…This study was part of a longitudinal and open-label trial using ketamine for depression, conducted at the Affiliated Brain Hospital of Guangzhou Medical University (Chen et al, 2021;Zheng et al, 2020)…”
Section: Participantsmentioning
confidence: 99%
“…Another N-methyl-D-aspartate receptor (NMDAR) antagonist, memantine, could reverse anhedonia and increase BDNF concentrations in the prefrontal cortex [ 23 ]. The role of BDNF in the antisuicidal and antidepressant effects of ketamine at a subanaesthetic dose has been investigated in depressed individuals [ 24 - 27 ]. For example, Zheng et al found that baseline plasma BDNF (pBDNF) concentrations could predict the final antidepressant response to six ketamine treatments [ 26 ].…”
Section: Introductionmentioning
confidence: 99%